"We are still doing some magic": Exploring the effectiveness of online therapeutic clowning. Issue 2 (4th May 2023) - Holland, Melissa; Fiorito, Maria-Elena; Gravel, Maï-Li; McLeod, Sarah; Polson, Jenna; Incio-Serra, Natalia; Blain-Moraes, Stefanie
ABSTRACT: Background: Therapeutic clowns use embodied practices to engage with clients, their families and healthcare staff to empower patients and create therapeutic relationships. This study explored the effectiveness of a virtual therapeutic clown initiative. Methods: Thirteen therapeutic clowns participated in a semi-structured interview to discuss their experiences with online clowning; additionally, four dyads consisting of a clown duo and a client explored multiple perspectives of a shared online clowning experience. Data were analyzed according to the six core competencies of therapeutic clowning. Results: Although all therapeutic clowns and caregivers reported challenges and limitations with the medium, virtual therapeutic clowning was effective for empowering clients and forming therapeutic relationships. Clowns successfully used many strategies to maintain their core clowning competencies in the virtual environment. Conclusions: Virtual clowning may be more beneficial for some clients than in-person clowning and has the potential to extend therapeutic clowning beyond its traditional domains of practice.